Biomarkers associating endothelial dysregulation in pediatric-onset systemic lupus erythematous - Wan-Fang Lee; Chao-Yi Wu; Huang-Yu Yang; Wen-I Lee; Li-Chen Chen; Liang-Shiou Ou; Jing-Long Huang (BMC, 2019)
Abstract Background/purpose Endothelium is a key element in the regulation of vascular homeostasis and its alteration can lead to the development of vascular diseases. Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with potential extensive vascular lesions, involving skin vessels, renal glomeruli, cardiovascular system, brain, lung alveoli, gastrointestinal tract vessels and more. We aimed to assess endothelial dysregulation related biomarkers in pediatric-onset SLE (pSLE) patient serum and elucidate its correlation with their clinical features, laboratory parameters, and the overall disease activity. Methods Disease activities were evaluated by SLE disease activity index (SLEDAI). Patient characteristics were obtained by retrospective chart review. Six biomarkers associated with endothelial dysregulation, including Angiopoietin-1 (Ang-1), Angiopoietin-2 (Ang-2), Tie2, Vascular endothelial growth factor (VEGF), thrombomodulin, and a disintegrin-like and metalloprotease with thrombospondin type 1 motif (ADAMTS13) were tested through enzyme-linked immunosorbent assay (ELISA) measurement. Results This study comprised 118 pSLE patients. Data from 40 age-matched healthy controls were also obtained. The mean diagnostic age was 13 ± 4.12 years-old and 90.7% are females. Serum levels of VEGF, Tie2, thrombomodulin were significantly higher while serum ADAMTS13 was lower in active pSLE patients when compared to those with inactive diseases (all p < 0.05). In organ specific association, serum thrombomodulin level was higher in pSLE patient with renal involvement, and serum ADAMTS13 levels was negatively associated with neurological involvement (p < 0.05). A cutoff of thrombomodulin at 3333.6 pg/ml best correlated renal involvement. (AUC = 0.752, p < 0.01). Conclusion Endothelial dysregulation associating proteins seems to be potent biomarkers for pSLE activity as well as organ involvement in pSLE patients. These biomarkers may be beneficial in understanding of the vascular pathogenesis and disease monitoring.